PENGARUH AKTIVITAS TAMBANG APUNG TERHADAP KEANEKARAGAMAN IKAN DI PERAIRAN SUNGAI PAKIL, BANGKA - AHMAD ZULFIKRI; UMROH UMROH; EVA UTAMI (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2016)
Tin mining in River Pakil used by floating mining. Mining activities would negatively effect to water quality and threaten biodiversity of fish resources. This study aims to know fish diversity in River Pakil and to analyze fish diversity differences between River Pakil and River Pembalu.. The experiment was conducted in January until February 2016 in Pakil and Pembalu river. This study using purposive sampling method with a set of three stations represent the (upstream, midstream and downstream). Fishing gear used for sampling fish are gill nets, traps and scoop. Results showed 378 individuals and 6 species 9 families of fish found in Pakil River, While results obtained 1590 individuals and 8 species 15 families of fish found in Pembalu River. Fish Diversity in Pembalu River are between 0,179 – 2,015 but fish diversity in Pakil River are between 0,232 – 1,672. River that has mining activities influenced have less species of fish than natural river.